EHD flow auxiliary particle collection in HVDC electrostatic precipitator based on PIV flow visualization technology. (1st April 2023) - Yan, Dongjie; Zhang, Xiaohai; Li, Zhenqiang; Abbas, Ghulam; Yu, Ya; Zhang, Ziang
Abstract: The electrostatic precipitator (ESP) is modified with the aid of an EHD flow in high voltage direct current (HVDC) to trap submicron-sized and ultra-high resistivity particles. In this study, the modified method for micron spherical silica was developed and optimized by particle image velocimetry (PIV) and numerical simulation. Meanwhile, scattering images of particle movement were obtained by laser and CCD camera. These results showed that the fine particles were driven by EHD flow towards the cavity. The D50 and D90 of particles measured by using the SYNC-type particle size analyzer inside the auxiliary dust removal cavity were 0.635 μ m and 1.178 μ m, which were much smaller than those of the particles deposited on the rear side of the cavity. The particle morphology was observed by scanning electron microscope (SEM), which indicated that multi-layer particles were agglomerating on the surface of the plate electrodes. However, particles were distributed in loose mono-layer in the cavity with no obvious agglomeration. The results showed that the modified method improved the efficiency.